Current mode multi scroll chaotic oscillator based on CDTA - Lin, Yuan; Gong, Junhui; Yu, Fei; Huang, Yuanyuan (Frontiers in Physics, 2023)
Compared to voltage mode circuits, current mode circuits have advantages such as large dynamic range, fast speed, wide frequency band, and good linearity. In recent years, the development of call flow modeling technology has been rapid and has become an important foundation for analog integrated circuits. In this paper, a current mode chaotic oscillation circuit based on current differential transconductance amplifier (CDTA) is proposed. This proposed circuit fully utilizes the advantages of current differential transconductance amplifier: a current input and output device with a large dynamic range, virtual ground at the input, extremely low input impedance, and high output impedance. The linear and non-linear parts of the proposed circuit operate in current mode, enabling a true current mode multi scroll chaotic circuit. Pspice simulation results show that the current mode chaotic circuit proposed can generate multi scroll chaotic attractors.